The Effectiveness of Endophytic Fungi Origin of Potato Plant Roots in Coffee Skin Compost Media to Suppress Development of Potato Leaf Disease (Phytophtora infestans) - Anna Fitriana; Lukman Hakim; Marlina Marlina (Budapest International Research and Critics University, 2020)
Potato leaf blight is caused by Phytophthora infestans fungus is one of the important diseases in potato plants. The decrease in potato production due to P. infestans can reach 90%. Until now, P. infestans pathogen attack is an important problem and there is no fungicide that is really effective against the disease. This study aims to examine the effectiveness of endophytic fungi from potato roots in suppressing the development of P. infestans potato leaf blight disease carried out at University Farm Stasiun Riset Bener Meriah (UFBM) Syiah Kuala University Tunyang Village, Timang Gajah District, Bener Meriah Regency from May to October 2014. The method used is the experimental method. The results of this study indicate that endophytic fungi from the roots of potato plants in coffee skin compost media can suppress the development of leaf blight caused by P. infestans, endophytic fungi from potato plant roots in coffee skin compost media. The best results were found in B9 endophytic fungi isolates with the intensity of the pathogen attack P. infestans 48.00%, the intensity of damage to potato plants due to pathogen P. infestans and 2.60%, the weight of healthy tubers 332.4 grams.